An Examination of Text Complexity as Characterized by Readability and Cohesion. Issue 1 (2nd January 2016) - Reed, Deborah K.; Kershaw-Herrera, Sarah
Abstract : To better understand dimensions of text complexity and their effect on the comprehension of adolescents, 103 high school seniors were randomly assigned to 4 groups. Each group read versions of the same 2 informational passages and answered comprehension test items targeting factual recall and inferences of causal content. Group A passages had a challenging readability level and high cohesion; Group B passages had an easier readability and low cohesion; Group C passages had a challenging readability level and low cohesion; and Group D passages had an easier readability and high cohesion. Students in Group D significantly outperformed students in Group C ( g = 0.78). Although the effect sizes of comparisons among all groups ranged from g = 0.13 to 0.73, no other comparisons were statistically significant. Results indicate that adolescents' reading comprehension is dually influenced by a text's readability and cohesion. Implications for matching readers to instructional text are discussed.